The role of polymorphism of interleukin 2, 10, 13 and TNF-α genes in cutaneous T-cell lymphoma pathogenesis - Nedoszytko, Boguslaw; Olszewska, Berenika; Roszkiewicz, Jadwiga; Glen, Jolanta; Zabłotna, Monika; Ługowska-Umer, Hanna; Nowicki, Roman; Sokołowska-Wojdyło, Małgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : As the pathogenesis of cutaneous T-cell lymphomas (CTCL) is not fully understood, inherited gene polymorphisms are considered to play a role in the development of lymphomas. Aim : To investigate whether certain gene polymorphisms might be involved in the development of CTCL. Material and methods: In the case-control study we compared the frequency of nine selected single nucleotide polymorphisms (SNP) of seven genes ( rs1800587/–889 C/T of interleukin (IL)-1α, rs2069762/–330G/T ) and rs2069763/+166G/T of IL-2, rs1800925/–1112 C/T of IL-13, rs1800896/–1082 A/G of IL-10, rs4073/–251 A/T of IL-8, rs5370/K198N, rs180054/–1370T/G of endothelin-1 and rs1800629/–308 G/A of TNF-α) in 43 CTCL and Polish cases using the amplification refractory mutation system polymerase chain reaction method. Results : We have found that two genotypes, –330GG of IL-2 and – 1112TT of IL-13 both promoter variants associated with “hypertranscription phenotype”, were over-represented in CTCL patients compared to healthy controls, and they increase the risk of malignancy development (OR = 5.82, p = 0.001 for IL-2 –330 GG, and OR = 5.67, p = 0.0024 for IL-13 –1112 TT). On the other hand, high transcription –308A allele of the TNF-α gene and –1082GG of IL-10 genotype is less frequent in lymphoma patients and has protective effects on the development of CTCL (OR = 0.45, p = 0.0466 for –308A of TNF-α, and OR = 0.35, p = 0.0329 for –1082GG of IL-10 genes). Conclusions : Our results indicate that hypertranscription promoter variants of IL-2 and IL-13 genes could be estimated as the risk factor for development of CTCL, while TNF-α and IL-10 variants have a protective effect.